Systematic revision of Anopinella Powell (Lepidoptera: Tortricidae: Euliini) and phylogenetic analysis of the Apolychrosis group of genera - Brown, John W.; Adamski, David (Zootaxa, 2003)
Thirty-five species are recognized in the Neotropical genus Anopinella Powell, including 5 previously described, A. isodelta (Meyrick), A. triquetra (Walsingham), A. ophiodes (Walsingham), A. aurea (Razowski & Becker), new combination, and A. perblanda (Razowski & Becker), new combination, and 30 described as new: A. albolinea (TL: Costa Rica), A. araguana (TL: Venezuela), A. arenalana (TL: Costa Rica), A. boliviana (TL: Bolivia), A. brasiliana (TL: Brazil), A. cafrosana (TL: Costa Rica), A. cartagoa (TL: Costa Rica), A. carabayana (TL: Peru), A. choko (TL: Colombia), A. cuzco (TL: Peru), A. fana (TL: Venezuela), A. holandia (TL: Guatemala), A. larana (TL: Venezuela), A. macrosema (TL: Costa Rica), A. mariana (TL: Guatemala), A. panamana (TL: Panama), A. parambana (TL: Ecuador), A. peruvensis (TL: Peru), A. phillipsae (TL: Costa Rica), A. porrasa (TL: Costa Rica), A. powelli (TL: Costa Rica), A. rastafariana (TL: Jamaica), A. razowskii (TL: Brazil), A. rica (TL: Costa Rica), A. rigidana (TL: Costa Rica), A. styraxivora (TL: Costa Rica), A. sympatrica (TL: Guatemala), A. tinalandana (TL: Ecuador), A. transecta (TL: Costa Rica), and A. tucki (TL: Peru). The genus occurs from Jamaica and southern Mexico to southern Brazil, Paraguay, and Bolivia. One species has been reared from the fruit of Styrax (Styracaceae), one from a fungus gall on Inga longispina (Fabaceae), and one from the stem of Vernonia (Asteraceae). We re-examine phylogenetic relationships among Anopinella and its putative related genera, Seticosta Razowski, Punctapinella Brown, Strophotina Brown, and Apolychrosis Amsel. We synonymize Ecuadorica Razowski & Becker, 2000, with Anopinella.